Evolution of Structure and Active Sites during the Synthesis of ZSM-5: From Amorphous to Fully Grown Structure - Silva, Laura Lorena [UNESP]; Cardoso, Dilson; Sievers, Carsten; Martins, Leandro [UNESP] (American Chemical Society (ACS), 2020)
Lately, to considerably reduce the diffusion constraints in the catalysis performed by zeolites, there has been significant interest in syntheses of partially formed zeolites with extremely accessible active sites, named embryonic zeolites. Their preparation relies on stopping the crystallization of conventional micron-sized zeolites before the zeolites reach full-crystallization, as detected by X-ray diffraction. In this current study, ZSM-5 zeolites were synthesized by using the same starting batch without an organic template and different times, obtaining amorphous, ill-crystallized, and fully grown structures that were characterized by various physicochemical methods and used in two catalytic test reactions. Using this synthesis strategy, two significant features of zeolites in catalysis are highlighted: (1) the accessibility of their inner pores for reactants and (2) the confinement effect, that is, the ability of zeolites to stabilize transition states in some catalytic reactions. As the ZSM-5 was being formed, it had a decreased activity for glycerol condensation with acetone, indicating steric restrictions to the bulky product that has a kinetic diameter (0.63 nm) considerably higher than the zeolite micropores (0.51 × 0.54 nm). On the other hand, the catalytic activity for methanol dehydration to dimethyl ether was proportional to crystallinity, as dimethyl ether intermediates adsorb within the zeolite cavities that tend to reciprocally enhance interactions giving an optimal effect in the catalytic property.